Simultaneous Estimation of Paracetamol and Valdecoxib in Combined Dosage Forms by RP-HPLC Method - SENTHAMIL SELVAN, P.; GOPINATH, R.; SARAVANAN, V.S.; PERIYASAMY, K. (Asian Journal of Chemistry, 2010)
A simple, selective, rapid, precise and economical reversed phase high performance liquid chromatography (RP-HPLC) method has been developed for the simultaneous estimation of paracetamol and valdecoxib from tablets. The method was carried out on a Phenomenex Gemini C18 (25 cm × 4.6 mm i.d., 5 μ) column with a mobile phase consisting of acetonitrile: 20 mM octane sulphonic acid (adjusted to pH 3.0 using orthophosphoric acid) (50:50 v/v) at a flow rate of 1.0 mL/min. Detection was carried out at 250 nm. Bromhexine was used as an internal standard. The retention time of paracetamol, bromhexine and valdecoxib were 2.97, 5.85 and 8.05 min, respectively. The validation of the proposed method was also carried out according to ICH guidelines.